Bidayatul mujtahid - Ibnu_Rusyd (Bulan Bintang, 1969)
tr, Jil. I=c.1-4; Jil. IV=c.1; Jil. V=c.1-3; Jil. VI=c.1; Jil.IX=c.1/oen, Jil.X=c.1/tr,jil.1=c.5/ast jil.4 =c.2/ast jil.1 =c.6-7/ir, jil.IV,c.3 ; jil.IX,c.2/ast jil.4=c.4